GENETIC AND INFECTIOUS FACTORS PREDISPOSING TO OSTEOPENIA - Hurtova, Y.M.; Dienha, O.V.; Dienga, A.E.; Litovkin, K.V.; Pyndus, T.O.; Pyndus, V.B.; Shnaider, S.A. (World of Medicine and Biology, 2023)
Osteopenia is a complex disease associated with decreased bone mineral density and characterized by a moderate risk of fracture, which in certain situations can lead to osteoporosis. Identification of predisposition factors for osteopenia may help to individualize prognosis, treatment, and prevention of fractures and their adverse outcomes. The purpose of this study was to examine the association of single-nucleotide polymorphisms of the TNFSF11, TNFRSF11B, SOST, ZNF385B, and LRP5 genes involved in bone metabolism and Porphyromonas gingivalis oral infection with risk for osteopenia. The study group included 18 patients with osteopenia. The control group included 18 people without osteopenia. The T-allele polymorphism of the TNFRSF11B gene increased the risk of osteopenia in allelic, dominant, and recessive inheritance models, while the A-allele polymorphism of the ZNF385B gene – in allelic and dominant inheritance models. The number of bacteria in the gingival sulcus fluid samples of patients with osteopenia significantly exceeded the same indicator in the control group